2021
DOI: 10.3389/fphys.2021.761411
|View full text |Cite
|
Sign up to set email alerts
|

Blood Rheological Characterization of β-Thalassemia Trait and Iron Deficiency Anemia Using Front Microrheometry

Abstract: The purpose of this work is to develop a hematocrit-independent method for the detection of beta-thalassemia trait (β-TT) and iron deficiency anemia (IDA), through the rheological characterization of whole blood samples from different donors. The results obtained herein are the basis for the development of a front microrheometry point-of-care device for the diagnosis and clinical follow-up of β-TT patients suffering hematological diseases and alterations in the morphology of the red blood cell (RBC). The visco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…Diseases such as malaria [ 49 , 50 , 51 ], sickle cell anemia [ 52 , 53 ], diabetes [ 54 ], and hemolytic syndromes [ 55 , 56 , 57 ], which affect the biomechanical properties, have shown differences in the expected values of their blood viscosities as they flow at a fixed shear rate. These altered values of the viscosity are due to a decrease in the concentration of red blood cells, to an increase of the rigidity of the membrane of red blood cell, or to alterations in the aggregation process.…”
Section: Introductionmentioning
confidence: 99%
“…Diseases such as malaria [ 49 , 50 , 51 ], sickle cell anemia [ 52 , 53 ], diabetes [ 54 ], and hemolytic syndromes [ 55 , 56 , 57 ], which affect the biomechanical properties, have shown differences in the expected values of their blood viscosities as they flow at a fixed shear rate. These altered values of the viscosity are due to a decrease in the concentration of red blood cells, to an increase of the rigidity of the membrane of red blood cell, or to alterations in the aggregation process.…”
Section: Introductionmentioning
confidence: 99%
“…The differentiation between TT and IDA using simple, fast, and low economic cost technologies has been of high concern in recent years. For instance, a previous study suggests that the Mentzer index (MCV/RBC) is able to differentiate between patients with β‐TT and IDA with a sensitivity and specificity of 91% and 83%, respectively, in pregnant women 6 . Another study evaluated the capability of optical RBC technology for discriminating patients with β‐TT and IDA and revealed that the RBC concentration has the best discriminative value with an AUC of 0.963, followed by the RBC distribution width in the size distribution with an AUC of 0.960 and the RBC distribution width coefficient of variation with an AUC of 0.924 34 .…”
Section: Discussionmentioning
confidence: 99%
“…TT is a hereditary disease that is characterized by the aberrant synthesis of hemoglobin beta chain due to genetic abnormality, whereas IDA is characterized by the insufficiency of healthy red blood cells (RBCs) because of the lack of iron 2,3 . However, TT and IDA share some common clinical presentations, and it is challenging to differentiate between TT and IDA using regular laboratory examinations and the clinical symptoms of the patients 4–7 . Clinically, if IDA is misdiagnosed as TT, clinicians may neglect supplementation with iron and further investigate the real etiology.…”
Section: Introductionmentioning
confidence: 99%
“…RBC deformability in thalassaemia is not well known. Recently, we have demonstrated that beta-thalassaemia (β-thal and δβ-thal) shows a characteristic left shift of osmoscan curve that is different from iron deficiency anaemia [77,78]. Probably, the decrease of one globin chain synthesis may lead to the imbalance of the α/β chains equilibrium and to the overproduction of the normal chain that may increase RBC dehydration and rigidity [8,78,79].…”
Section: Thalassaemiamentioning
confidence: 99%